PERANCANGAN KOMIK EDUKASI “RACHEL’S GUITAR ADVENTURE” SEBAGAI MEDIA MOTIVASI PENTINGNYA MEMILIKI CITA-CITA UNTUK REMAJA - IHSAN HUSANDI, Hendra Afriwan, S.Sn., M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The lack of spirit and motivation to develop self-potential in order to prepare a bright future in accordance of ideals or future goals making teenagers tend to fill the spare time with unproductive activities. One of  the few factors that cause this happening is entertainment media that is not educational. Focus, time and  energy of adolescents distracted from the important things such as learning, selfdevelopment and future preparation.In Rachel's Guitar Adventure comic design process, the author collected the data through observation,  literature studies and empirical experiences from the author himself. The data is processed through the  5W1H method. The results of the analysis are used as reference in designing the characters and writing  stories under fictional drama genre. The comic was made with digital techniques using Wacom Intuos  tablet through the Paint Tool Sai and Adobe Photoshop. The style of illustration is semi-realist which is arranged in a closed and open panel variation. Rachel’s Guitar Adventure was printed as a full-color comic book with total of 36 pages on A5 art paper. This design is also supported by additional media such as  T-shirts, note books, mugs, pins, stickers, posters and x-banners.Keywords: Education, Motivation, Comic, Ideals